The Influence Of Financial Literacy and Accounting Technology on The Sustainability OF MSMEs - Lindayani Ritonga (Cita konsultindo, 2026)
Negotiation is Study This aim For analyze influence Literacy finance and technology accountancy to Sustainability of Micro, Small, and Medium Enterprises (MSMEs). Research methods used is approach quantitative with technique analysis multiple linear regression. Primary data obtained of 74 MSME actors through questionnaire based Likert scale. Analysis results show that literacy finance and technology accountancy own influence positive and significant to sustainability of MSMEs, with mark coefficient determination (R²) of 0.65. Findings This indicates that improvement understanding to draft finance as well as utilization technology accountancy can strengthen Power resistance and capacity growth of MSMEs in face challenge business. Research This give recommendation strategic in the form of integration training literacy finance and technology accountancy to in a sustainable MSME empowerment program. With thus, it is hoped that MSMEs capable increase efficiency operational, transparency finance, and resilience business in a way comprehensive research​ this also opens room for studies continuation that explores other variables such as digital innovation and access financing as factor supporters sustainability of MSMEs.